Tata Kelola Rekam Medis Berbasis Elektronik dalam Mengklasifikasi Indeks Penyakit Pasien dengan Menggunakan Metode Agile - Nurkhotimah, Laila; Syahidin, Yuda; Gunawan, Erix (Program Studi Teknik Informatika Universitas Pamulang, 2023)
Through field research, it is known that the collection and processing of disease index data at Hospital X has been fully computerized and integrated into the hospital information management system. However, the process of entering disease index data for inpatients has not been automated, which slows down the production of disease index reports. The disease index is used to provide statistical reports on morbidity (unhealthy conditions) and summarize data on 10 significant cases of inpatient disease, so that the report is useful for hospitals and reporting to the Health Office, District, Province and the Ministry of Health. Electronic medical records are a key solution in the governance of hospital services. The main focus of this research project is to classify the disease index of patients in the inpatient installation using the agile method so as to produce a more computerized, integrated and automated disease indexing system. The agile method includes four stages including system requirements analysis, design, coding, and testing. The agile method makes system planning more flexible and can be adapted to changes in user needs as they develop over time. As a result, applying the agile method to the design of the system built will increase the accuracy of disease categorization in inpatients and help the medical team provide more optimal care and treatment and medical records officers can be maximized in collecting data and preparing disease index reports.